(untitled) (American Journal of Food Science and Technology, 2023)
The formulation of high nutritional quality composite flour for use in producing bakery products is essential and advantageous health wise to consumers of these products. Therefore in this study, various formulated ratios (0:100, 10:90, 20:80, 30:70, 40:60, 50:50, 60:40, 70:30, 80:20, 90:10, and 100:0 denoted as A2, B9, B8, B7, B6, B5, B4, B3, B2, B1 and A1 respectively) of wheat and sologold sweet potato flour were made. The pure wheat A1 and pure sologold sweet potato A2 served as basis of assessing the nutritional contribution of sologold sweet potato flour at various ratios with wheat flour. The proximate properties, mineral, vitamins and beta carotene were determined in the various ratios formulated. More so, the best blend was selected based on desirability index of the formulated composite flours. Results revealed that B6 (40% wheat and 60% sologold sweet potato) had the highest desirability index of 0.65164. Hence, was selected as the best blend (composite) flour. The nutritional profile of the chosen B6 sample are as follows: moisture content (10.12%), crude fiber (3.21%), ash content (2.61%), protein content (5.80%), oil extract (5.20%), NFE (74.10%), sodium (0.13mg/g), calcium (2.08mg/g), magnesium (0.07mg/g), potassium (2.14mg/g), vitamin C (0.30µg/g), Vitamin A (24.6µg/g) and beta-carotene content (27.5µg/g). This profile showed valuable positive impact of sologold sweet potato flour on the nutritional characteristics of the developed B6 composite flour. Comparison of the blend B6 with some existing formulated composite flours, revealed that the developed composite flour B6 will likely have added advantage to the well-being of those that will consume its bakery products. Thus the B6 Blend (composite) flour is recommended for use in baking.